A small, narrow‐beaked albatross from the Pliocene of New Zealand demonstrates a higher past diversity in the feeding ecology of the Diomedeidae. (16th July 2019) - Mayr, Gerald; Tennyson, Alan J. D.
Abstract : We describe a nearly complete, three‐dimensionally preserved skull of a new albatross species from the late Pliocene (3.0–3.4 million years ago) Tangahoe Formation of New Zealand. Aldiomedes angustirostris, n. gen. et sp. has only about 90% of the length of the skull of the smallest extant albatross and is the geologically youngest record of a small‐sized albatross known to date. The new species is characterized by a mediolaterally compressed beak, which is not found in any living albatross. The small size and some cranial features of A. angustirostris indicate that, in spite of its comparatively young geological age, the new species was not part of crown group Diomedeidae. We hypothesize that A. angustirostris was more piscivorous than extant albatrosses, which predominantly feed on squid. The reasons for the extinction of smaller‐sized albatrosses are elusive but may be related to changes in seabird fauna during the Pliocene epoch, which witnessed the radiation of various non‐procellariiform seabird groups.